TCH-011 Development of Pyridoxal-5-Phosphate Hard Capsules For Paediatric Use. (12th March 2013) - Serrano, C; Joret, P; Siorat, V; Vaconsin, P; Abarou, T; Storme, T
Abstract : Background: The active form of vitamin B6, called pyridoxal-5-phosphate (P5P), is an essential cofactor for several enzymes involved in various pathways of intermediary metabolism. PNPO is the rate-limiting enzyme in the synthesis of pyridoxal from vitamin B6 and a lack of activity causes dependency on an external source of pyridoxal. Epileptic seizure is the clinical outcome of P5P deficiency. Purpose: To provide a dosage form suitable for newborns and children. Capsules containing standardised P5P were compounded. Moreover, a fully soluble powder blend was formulated to fill the capsules and a method to determine the stability of the P5P content was developed. Materials and Methods: Dissolution assays were performed using oral syringes as nurses do. Time to complete dissolution and concentration were determined at each test. P5P content was determined by HPLC-UV (205 nm). The mobile phase consisted of phosphate buffer (0.05 M; pH 2.6) at a flow rate of 1 ml/min. The right active ingredient was tested by adding vitamin B6 to samples. Degradation by-products in stress conditions were also determined. The method was validated according to ICH recommendations. Results: Strengths were standardised at 10, 25, 50, 100 or 250 mg/capsule. The adopted blend is quickly solubilised in water and has a sweet taste. The HPLC readings were linear (r² = 0.9994) at the wavelength used, indicating good reproducibility and repeatability (SD = 0.46%). No matrix effect due to the diluent was observed. Conclusions: As P5P is a low toxicity compound, a test treatment with P5P is given to every newborn with idiopathic seizure before any treatment with standard antiepileptics. This method allows rapid routine assay of P5P. Stability testing of 3 compounded batches is ongoing. No conflict of interest.